A clearing in the objectivity of aesthetics? - Lee, Daniel H.; Chikazoe, Junichi (Frontiers in Neuroimaging, 2023)
As subjective experiences go, beauty matters. Although aesthetics has long been a topic of study, research in this area has not resulted in a level of interest and progress commensurate with its import. Here, we briefly discuss two recent advances, one computational and one neuroscientific, and their pertinence to aesthetic processing. First, we hypothesize that deep neural networks provide the capacity to model representations essential to aesthetic experiences. Second, we highlight the principal gradient as an axis of information processing that is potentially key to examining where and how aesthetic processing takes place in the brain. In concert with established neuroimaging tools, we suggest that these advances may cultivate a new frontier in the understanding of our aesthetic experiences.